Application of thermosensitive-hydrogel combined with dental pulp stem cells on the injured fallopian tube mucosa in an animal model - Luo, Lihua; Zhu, Qunyan; Li, Yejian; Hu, Fengting; Yu, Jiangtao; Liao, Xiangyan; Xing, Zhenjie; He, Yan; Ye, Qingsong (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: Fallopian tube (FT) injury is an important factor that can lead to tubal infertility. Stem-cell-based therapy shows great potential for the treatment of injured fallopian tube. However, little research has shown that mesenchymal stem cells (MSCs) can be used to treat fallopian tube damage by in situ injection. In this study, we in situ transplanted PF127 hydrogel encapsulating dental pulp stem cells (DPSCs) into the injured sites to promote the repair and regeneration of fallopian tube injury. Materials and methods: The properties of dental pulp stem cells were evaluated by flow cytometry, immunofluorescence analysis, and multi-differentiation detection. The immunomodulatory and angiogenic characteristics of dental pulp stem cells were analyzed on the basis of the detection of inflammatory factor expression and the formation of capillary-like structures, respectively. The biocompatibility of PF127 hydrogel was evaluated by using Live/Dead and CCK-8 assays. The effects of PF127 hydrogel containing dental pulp stem cells on the repair and regeneration of fallopian tube injury were evaluated by histological analysis [e.g., hematoxylin and eosin (H&E) and Masson’s trichrome staining, TUNEL staining, immunofluorescence staining, and immunohistochemistry], Enzyme-linked immunosorbent assay (ELISA), and RT-PCR detections. Results: Dental pulp stem cells had MSC-like characteristics and great immunomodulatory and angiogenic properties. PF127 hydrogel had a thermosensitive feature and great cytocompatibility with dental pulp stem cells. In addition, our results indicated that PF127 hydrogel containing dental pulp stem cells could promote the repair and regeneration of fallopian tube damage by inhibiting cell apoptosis, stimulating the secretion of angiogenic factors, promoting cell proliferation, modulating the secretion of inflammatory factors, and restoring the secretion of epithelial cells. Conclusion: In this study, our results reported that in situ injection of PF127 hydrogel encapsulating dental pulp stem cells into the injured sites could provide an attractive strategy for the future treatment of fallopian tube injury in clinical settings.